Combining Ability of Maize Landraces for Yield and Basic Chemical Composition of Grain - Aleksandar Popović; Vojka Babić; Zoran Čamdžija; Srboljub Živanov; Dragana Branković-Radojčić; Jelena Golijan Pantović; Vesna Perić (Agronomy)
The launch of a successful quality-oriented breeding program requires both mining the residual diversity in grain quality parameters contained in the elite, high-yielding breeding material with good agronomic performance and introgression of new germplasm, such as local landraces, with a high level of targeted quality parameters per se. This study analyzed the combining abilities of 31 maize landraces and two divergent inbred lines–testers (ZPL217 and ZPL-255/75-5) regarding the yield and protein, starch, and lipid content, assessed by Near Infrared Reflectance (NIR) spectroscopy as a fast, non-destructive, and cost-effective method. The general combining ability (GCA) defines the average behavior of genotype in hybrid combination, resulting from additive gene action, so positive GCA values of landraces AN13 and AN197 for protein, AN632 for lipids, and AN594 for starch content indicate that they can be valuable sources of the mentioned properties in quality-oriented maize breeding programs. The obtained correlation between starch content and protein and yield (−0.948 **; 0.587 **) pointed out that an increase in the protein content during breeding will be accompanied by a decrease in the starch content and yield. The specific combining ability (SCA) of the testers used, suggests their possible application in establishing and improving quality breeding programs’ initial material.